MEDITATION AND ITS IMPACT ON PSYCHOLOGICAL HEALTH - Maurya, Shivangi; Singh, K.N.; Singh, G. (International Journal of Ayurveda and Pharma Research, 2015)
In the present era, our society is facing challenges of hurries and worries. In the present scenario society is using the mechanical appliances and electronic gadgets for simplifying their life. Society is unable to get peace and facing lots of physical and psychological problems. Self realization and self satisfaction can be achieved by the practice of meditation. Present paper is an effort to provide some solutions regarding the problem. This review article has been completed by the help of different studies which are carried out in this area. Meditation is a practice in which an individual trains the mind or induces a mode of consciousness, either to realize some benefit or as an end in itself. A particularly ambitious form of meditation aims at effortlessly sustained single-pointed concentration single-pointed analysis, meant to enable its practitioner to enjoy an indestructible sense of well-being while engaging in any life activity. As a result of excess mental stuffing engagements and burden of scientism, people face mental and physical inefficiency and fatigue that manifest numerous physical and mental disorders/problems and diseases. Now the science itself is advocating people / sufferer that they should go back to spirituality from where actually we had started growing, to attain normal state of physical and mental health and to ensure total well being. In this paper different aspects of meditation and mechanisms of meditation are considered. In the present paper the modern psychology has categorized different factors of the mind. Further the impact and benefits of meditation are highlighted.